How Does Work Motivation Impact Employees’ Investment at Work and Their Job Engagement? A Moderated-Moderation Perspective Through an International Lens - Shkoler, Or; Kimura, Takuma (Frontiers in Psychology, 2020)
This paper is aimed at shedding light on the effects of intrinsic and extrinsic motivation, as predictors have on Heavy-Work Investment of time and efforts and Job Engagement. By using a questionnaire survey, this study conducted a moderated-moderation analysis, considering two conditional effects – worker’s status (working students vs. non-student employees) and country (Israel vs. Japan) as potential moderators, since there are clear cultural differences between these countries. Data were gathered from 242 Israeli and 171 Japanese participants. The analyses revealed that worker’s status moderates the effects of intrinsic and extrinsic motivation on Heavy-Work Investment of time and efforts and job engagement and that the moderating effects were conditioned by country differences. Theoretical and practical implications and future research suggestions are discussed.